Аналіз рівнів експресії генів альфа-тубуліну під час холодової аклімації у ярої та озимої пшениці - Буй, Д.Д.; Пірко, Я.В.; Блюм, Я.Б. (Фактори експериментальної еволюції організмів, 2015)
Aims. Cereals, such as wheat (Triticum aestivum L.), display significant increase in freezing tolerance during a period of cold acclimation (CA). Unravel functions and regulations of CA-associated genes can help in receiving cold-resistant cultivars using biotechnology methods. It have identified potentially important for CA tubulin gene, such as TUBA-2- 3, which is assumed to be essential in forming cold-tolerant microtubules. Methods. Cold acclimation during 72 h was conducted. The level of TUBA-2-3 mRNA was measured using RT Real-time PCR with specific primers. Results. Similar patterns of expression alterations were observed on both winter and spring cultivar. The level of expression TUBA-2-3 decreased at day 1 and was strongly increased at day 2–3 for winter cultivar. Gene expression gradually increased at day 1–3 for spring cultivar. Conclusion. Differences in expression patterns between winter and spring cultivar were found, which leads to different level of winter and spring wheat cold tolerance.